Preparation of Value-added Chemicals via Chemical Looping Pyrolysis of Corn Straws with Ca-Fe Composite Oxygen Carrier - Li, Wenyao; Zhao, Longxin; He, Xiao; Liu, Jingjing; Liu, Yongzhuo; Guo, Qingjie (Fine Chemical Engineering, 2024)
Biomass chemical looping pyrolysis (BCLPy), which utilizes either reduced or oxidized oxygen carriers for biomass pyrolysis, enables the simultaneous production of high-quality bio-oils and clean syngas. In this study, CLPy of corn straws with a Ca-Fe composite oxygen carrier was investigated to produce value-added chemicals by optimizing both temperature and the mass ratio of oxygen carrier to biomass (OC/B). It has been demonstrated that the reduced Ca-Fe oxygen carrier (Re-OC) promotes hydrocarbon formation and facilitates removal of oxygenated compounds from bio-oils. Under optimal conditions (Re-OC/B = 4:3, T = 650 °C), the relative percentage of benzene, toluene and xylene (BTX) in the bio-oil reaches 27.0 area%, while that of 2-pentenone accounts for 38.0 area% at 550 °C with a Re-OC/B mass ratio of 1:3. The maximum yield based on corn straws approaches 4.7 wt.%. Regarding the oxidized Ca-Fe oxygen carrier (Ox-OC), the relative percentage of 2,3-dihydrobenzofuran (2,3-DHB) reaches a maximum value of 11.6 area% at 600 °C with an Ox-OC/B mass ratio of 2:3. Under catalytic ketonization of Ca2Fe2O5 oxygen carrier, a maximum value of 28.0 area% is achieved with an Ox-OC/B mass ratio of 4:3 at 450 °C. In summary, BCLPy provides a completely new strategy for producing biomass-derived chemicals with added value.